A mutation of MET, encoding hepatocyte growth factor receptor, is associated with human DFNB97 hearing loss. Issue 8 (4th May 2015) - Mujtaba, Ghulam; Schultz, Julie M; Imtiaz, Ayesha; Morell, Robert J; Friedman, Thomas B; Naz, Sadaf
Abstract : Background: Hearing loss is a heterogeneous neurosensory disorder. Mutations of 56 genes are reported to cause recessively inherited non-syndromic deafness. Objective: We sought to identify the genetic lesion causing hearing loss segregating in a large consanguineous Pakistani family. Methods and results: Mutations of GJB2 and all other genes reported to underlie recessive deafness were ruled out as the cause of the phenotype in the affected members of the participating family. Homozygosity mapping with a dense array of one million SNP markers allowed us to map the gene for recessively inherited severe hearing loss to chromosome 7q31.2, defining a new deafness locus designated DFNB97 (maximum logarithm of the odds score of 4.8). Whole-exome sequencing revealed a novel missense mutation c.2521T>G (p.F841V) in MET (mesenchymal epithelial transition factor), which encodes the receptor for hepatocyte growth factor. The mutation cosegregated with the hearing loss phenotype in the family and was absent from 800 chromosomes of ethnically matched control individuals as well as from 136 602 chromosomes in public databases of nucleotide variants. Analyses by multiple prediction programmes indicated that p.F841V likely damages MET function. Conclusions: We identified a missense mutation of MET, encoding the hepatocyte growth factor receptor, as a likely cause of hearing loss in humans.